2004
DOI: 10.1002/cncr.20423
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' expectations of experiencing treatment‐related side effects

Abstract: BACKGROUND Adequate management of treatment‐related side effects is important for patients and challenging for clinicians. Side effects generated by various treatments have been characterized reasonably well. However, to the authors' knowledge, less is known regarding what patients expect to experience regarding these side effects and how patient characteristics are related to these expectations. METHODS Patients with cancer (n = 1015 patients) from 17 Community Clinical Oncology Program (CCOP) institutions af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(51 citation statements)
references
References 28 publications
2
46
1
2
Order By: Relevance
“…This relationship is congruent with previous research which found older surgery patients to expect less intense post-surgical pain than younger patients (Gagliese, Jackson, Ritvo, Wowk, & Katz, 2000). In addition, our finding is consistent with a recent study of cancer patients about to begin treatment, in which patients over age 60 expected to experience fewer side effects during treatment than younger patients (Hofman et al, 2004). The positive correlation between education and expectancies for post-surgical fatigue is also consistent with the literature, which has found that patients with at least a high school degree expected greater fatigue than less educated patients (Hofman et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This relationship is congruent with previous research which found older surgery patients to expect less intense post-surgical pain than younger patients (Gagliese, Jackson, Ritvo, Wowk, & Katz, 2000). In addition, our finding is consistent with a recent study of cancer patients about to begin treatment, in which patients over age 60 expected to experience fewer side effects during treatment than younger patients (Hofman et al, 2004). The positive correlation between education and expectancies for post-surgical fatigue is also consistent with the literature, which has found that patients with at least a high school degree expected greater fatigue than less educated patients (Hofman et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Expectancies for treatment-related pain and fatigue are common among cancer patients (Hofman et al, 2004), and contribute to the subsequent experience of these taxing symptoms (Montgomery & Bovbjerg, 2004;Montgomery et al, 2002). Results of the present study indicated that: heightened distress on the day of surgery (prior to surgery) as well as heightened trait anxiety predicted higher expectancies for post-surgical pain and fatigue; having had the same surgical procedure in the past predicted lower expectancies for post-surgical fatigue; and higher levels of acute pre-surgical fatigue predicted higher expectancies for post-surgical fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, different authors refer to the importance of analyzing the emotional sphere of cancer patients, since it has been documented that one-third to one-half of adults with cancer suffer from significant experience of stress. [5,6] In studies about the emotional sphere of cancer patients, the National Comprehensive Cancer Network (NCCN) does not use the term stress in this context because it considers an unpleasant multifactorial emotional experience and psychological (cognitive and behavioral), social and/or spiritual nature that can interfere in the capacity to deal effectively with the disease, its physical symptoms and its treatment. [7] In the current research, the choice of the patient in chemotherapy as the focus of analysis was due to considering this treatment interference in the daily routine of the patients and its greater impact in the physical and emotional sphere and in the experience of the symptoms.…”
Section: Introductionmentioning
confidence: 99%